A dielectric metasurface optical chip for the generation of cold atoms - Zhu, Lingxiao; Liu, Xuan; Sain, Basudeb; Wang, Mengyao; Schlickriede, Christian; Tang, Yutao; Deng, Junhong; Li, Kingfai; Yang, Jun; Holynski, Michael; Zhang, Shuang; Zentgraf, Thomas; et al. (Science Advances)
Compact and robust cold atom sources are increasingly important for quantum research, especially for transferring cutting-edge quantum science into practical applications. In this study, we report on a novel scheme that uses a metasurface optical chip to replace the conventional bulky optical elements used to produce a cold atomic ensemble with a single incident laser beam, which is split by the metasurface into multiple beams of the desired polarization states. Atom numbers ~10 7 and temperatures (about 35 μK) of relevance to quantum sensing are achieved in a compact and robust fashion. Our work highlights the substantial progress toward fully integrated cold atom quantum devices by exploiting metasurface optical chips, which may have great potential in quantum sensing, quantum computing, and other areas.

Separation and reclamation of automotive hybrid structures made of metal and fibre-reinforced plastic - Schweizer, Swetlana; Becker-Staines, Anna; Tröster, Thomas (Waste Management)

Improving the performance of household refrigerating appliances through the integration of phase change materials in the context of the new global refrigerator standard IEC 62552:2015 - Sonnenrein, G.; Baumhögger, Elmar; Elsner, A.; Morbach, A.; Neukötter, M.; Paul, A.; Vrabec, J. (International Journal of Refrigeration)

Reliable Part-of-Speech Tagging of Historical Corpora through Set-Valued Prediction - Heid, Stefan Helmut; Wever, Marcel Dominik; Hüllermeier, Eyke (Journal of Data Mining and Digital Humanities)
Syntactic annotation of corpora in the form of part-of-speech (POS) tags is a key requirement for both linguistic research and subsequent automated natural language processing (NLP) tasks. This problem is commonly tackled using machine learning methods, i.e., by training a POS tagger on a sufficiently large corpus of labeled data. While the problem of POS tagging can essentially be considered as solved for modern languages, historical corpora turn out to be much more difficult, especially due to the lack of native speakers and sparsity of training data. Moreover, most texts have no sentences as we know them today, nor a common orthography. These irregularities render the task of automated POS tagging more difficult and error-prone. Under these circumstances, instead of forcing the POS tagger to predict and commit to a single tag, it should be enabled to express its uncertainty. In this paper, we consider POS tagging within the framework of set-valued prediction, which allows the POS tagger to express its uncertainty via predicting a set of candidate POS tags instead of guessing a single one. The goal is to guarantee a high confidence that the correct POS tag is included while keeping the number of candidates small. In our experimental study, we find that extending state-of-the-art POS taggers to set-valued prediction yields more precise and robust taggings, especially for unknown words, i.e., words not occurring in the training data.

Share price reactions to tariff imposition announcements in the Trump era - An event study of the trade conflict - Wengerek, Sascha Tobias
Employing a unique sample of 2,849 tariff imposition announcements by and against the United States (U.S.) over the period from 2018 to 2019, this study analyzes the impact of recent tariff announcements on share prices from 859 U.S. companies. We provide evidence for negative (cumulative) average abnormal stock returns due to tariff announcements during a symmetric three-day event window. We suggest that stock market investors expect adverse impacts of tariff impositions, e.g. a decrease in the companies' future cash flows and a threat of retaliation. The negative wealth effects are observed irrespective of whether the Trump administration announces safeguard tariffs to protect domestic firms or a retaliation is declared by foreign countries. Moreover, building several subsamples, we find that the adverse impact is mostly driven by announcements involving China and is associated with a variety of sector, tariff, trade and firm characteristics.
Keywords: event study; international relations; protectionism; strategic trade policy; tariffs; trade conflict

COVID-19 and investor behavior - Ortmann, Regina; Pelster, Matthias; Wengerek, Sascha Tobias (Finance Research Letters)

Sprachtechnologien für Digitale Assistenten - Haeb-Umbach, Reinhold (Studientexte zur Sprachkommunikation: Elektronische Sprachsignalverarbeitung 2020)
Keywords: Poster

Light backscattering from large clusters of densely packed irregular particles - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
We numerically simulate multiple light scattering in discrete disordered media represented by large clusters of irregular non-absorbing particles. The packing density of clusters is 0.5. With such conditions diffuse scattering is significantly reduced and light transport follows propagation channels that are determined by the particle size and topology of the medium. This kind of localization produces coherent backscattering intensity surge and enhanced negative polarization branch if compared to lower density samples.
Keywords: tet_topic_scattering

Forming tile shapes with simple robots - Gmyr, Robert; Hinnenthal, Kristian; Kostitsyna, Irina; Kuhn, Fabian; Rudolph, Dorian; Scheideler, Christian; Strothmann, Thim (Nat. Comput.)

Ansatz zur effizienteren Auslegung von Hybridbauteilen - Hielscher, Christian; Grenz, Julian; Camberg, Alan Adam; Wingenbach, Nils (ATZ - Automobiltechnische Zeitschrift)